The prevalence of partial edentulism and complete edentulism among adults and above population of Riyadh city in Saudi Arabia - Saleh M Almusallam; Mohammed A AlRafee (Journal of Family Medicine and Primary Care, 2020)
Objectives: The present study was conducted to investigate the prevalence of complete edentulism and partial edentulism among adults and above population in Riyadh city, in relation to gender, age, and education level. Baseline information related to edentulism will help us take action to promote oral health. Methods: A cross-sectional stratified cluster study was carried out in 2018–2019 in several dental care centers across Riyadh city. A total of 618 subjects aged 35–74 years were selected through convenient sampling and information related to edentulism was gathered followed by clinical examination. Results: Of the total sample, 349 (56.5%) were males and 261 (43.5%) were females. In the overall assessment of edentulism, it was found that the majority of the subjects 426 (69%) had one or more teeth missing. Among these subjects, there was (2.6%) who were completely edentulous, which represented (1.8%) of the total sample. Conclusion: A high percentage of adult patients have missing teeth and complete edentulism was found mostly in elderly people. Frequenting a dental center had an inverse relation with edentulism.